2022
DOI: 10.3390/genes13030464
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Modules and Genes Associated with Major Depressive Disorder in Adolescents

Abstract: Major depressive disorder (MDD) is a leading cause of disability worldwide. Adolescence is a crucial period for the occurrence and development of depression. There are essential distinctions between adolescent and adult depression patients, and the etiology of depressive disorder is unclear. The interactions of multiple genes in a co-expression network are likely to be involved in the physiopathology of MDD. In the present study, RNA-Seq data of mRNA were acquired from the peripheral blood of MDD in adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…In a recent review, the author suggested that RPS5KA might regulate key plasticity-related genes through epigenetic mechanisms to potentially avoid depression, which also supported our results [ 35 ]. As part of this neurotrophic factor cascades, MAPK signaling pathway and TNF signaling pathway might play a crucial role in immune and inflammatory response [ 36 , 37 ]. This agrees with the conclusions from previous studies that strong inflammation in MDD patients might be associated with drug resistance [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, the author suggested that RPS5KA might regulate key plasticity-related genes through epigenetic mechanisms to potentially avoid depression, which also supported our results [ 35 ]. As part of this neurotrophic factor cascades, MAPK signaling pathway and TNF signaling pathway might play a crucial role in immune and inflammatory response [ 36 , 37 ]. This agrees with the conclusions from previous studies that strong inflammation in MDD patients might be associated with drug resistance [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…62 Further, the genome-wide association analyses identified the 44 risk gene variants in MDD with 4 of them (namely LACC1, OLFM4, TIAF1, and NR4A2) being associated with immune responses. 63 Besides, a recent weighted gene co-expression network analysis (WGCNA) identified three genes related to immune responses (IL1RAP, UBE2W, and UBE2D1) as hub genes of adolescent 64 Further research involving genome-wide association studies, transcriptomics and WGCNA is needed to exactly shed light on the genetic contributions of inflammation-related depression.…”
Section: Genetic Contribution In the Relationship Between Inflammatio...mentioning
confidence: 99%
“… 63 Besides, a recent weighted gene co-expression network analysis (WGCNA) identified three genes related to immune responses ( IL1RAP, UBE2W, and UBE2D1 ) as hub genes of adolescent MDD. 64 Further research involving genome-wide association studies, transcriptomics and WGCNA is needed to exactly shed light on the genetic contributions of inflammation-related depression.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this review showed: a positive correlation between an upregulated expression of pro-inflammatory genes with the presence of MDD together with an altered expression of stress-related genes in MDD patients [ 33 ]. However, it is noteworthy to mention that the majority of the studies investigating gene expression in MDD were conducted so far in adult individuals, whereas only a small number of them included adolescents [ 31 , 34 36 ]. Nevertheless, similar findings between adults’ and adolescents’ transcriptomic profiles have been observed, specifically a dysregulation of inflammatory-related pathways and genes in both adults and adolescents with depression [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, similar findings between adults’ and adolescents’ transcriptomic profiles have been observed, specifically a dysregulation of inflammatory-related pathways and genes in both adults and adolescents with depression [ 33 ]. Among the studies conducted in adolescents, Zhao and colleagues identified enrichments in genes involved in apoptosis, TNF signaling pathway, and NF-kb signaling pathway in MDD adolescents compared with controls [ 36 ], and the study by Chiang and colleagues observed an up-regulation of inflammation-related genes and a down-regulation of antiviral-related genes in adolescents with depression compared with their non-depressed peers [ 34 ].…”
Section: Introductionmentioning
confidence: 99%